Networks, Labour and Migration among Indian Muslim Artisans - Chambers, Thomas (Book collections on Project MUSE., 2020)
Networks, Labour and Migration Among Indian Muslim Artisans provides an ethnography of life, work and migration in a North Indian Muslim-dominated woodworking industry.